An Analysis of Idioms in Sumbawanese Songs - Susilawati, Imas; Sartika, Sartika; Solihin, Solihin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research aimed to find out the meanings and types of idioms contained in 18 Sumbawanese songs. The method used in this study was the qualitative descriptive method. Research data were obtained through interview, documentation, and recording. In the analysis, the theory used was Leech theory (1974) to categorize the types of idiom meanings and the researchers focused on two types of meanings namely denotative and connotative meanings. In addition to this theory, the researchers also used Sudaryat's theory (2011) to classify the types of idioms contained in the 18 Sumbawanese songs. Based on the analysis, it was found that there were 18 idioms from 18 songs that were subject to research. Then from 18 idioms, 5 idioms belong to partial idioms and 13 idioms include full idioms.